Prevalence, pattern and correlates of work-related musculoskeletal disorders among school teachers in Enugu, Nigeria. Issue 1 (2nd January 2021) - Ojukwu, Chidiebele Petronilla; Anyanwu, Godson Emeka; Eze, Benjamin; Chukwu, Sylvester Caesar; Onuchukwu, Chioma Linda; Anekwu, Emelie Morris
Abstract : Introduction . There is insufficient literature on the prevalence of and risk factors for work-related musculoskeletal disorders (MSDs) among teachers in Nigeria. This study aimed to investigate the prevalence of work-related MSDs and their associations with occupational and socio-demographic factors of Nigerian-based school teachers. Materials and methods . Socio-demographic and occupational characteristics, prevalence and pattern of work-related MSDs of 352 school teachers (age 24–60 years) were investigated using a standard Nordic questionnaire. Data were summarized with descriptive statistics. Univariate and multivariate analyses were used to assess predictors of work-related MSDs. Results . The results showed that 70.2% of the teachers had work-related MSDs predominantly in the shoulder (62.3%) and neck (57.9%) regions. Most of the studied socio-demographic features and anthropometric and occupational characteristics were significantly associated ( p  < 0.05) with MSDs in at least one body region. Conclusions . There was a prevalence of work-related MSDs among the teachers. Advanced educational qualification, elevated teaching boards, teaching experience over 10 years and age range of 35–50 years were the major predictors of MSDs.